DOZ047.100: Impact of fundoplication on pH-MII tracings in pediatric patients with esophageal atresia. (24th June 2019) - Busoni, V; Sabban, J C; Lobos, P; Ursino, F; Urquizo, M; De la Iglesia, P; Orsi, M
Abstract: Introduction: Gastroesophageal reflux disease (GERD) is the most common long-term complication in esophageal atresia (EA) patients. Fundoplication in EA is controversial but may be an option in those with maximum GER therapy failure, acute life-threatening event, failure to thrive, persistent esophagitis, and recurrent anastomotic stenosis. Aim: The aim of this study was to compare GERD characteristics according pH-MII parameters in EA patients with and without fundoplication. Materials and Methods: Retrospective review of pH-MII tracings performed at a Gastroenterology Unit between 2011 and 2018 was carried out. Inclusion criteria were children under 18 years with history of EA, with and without fundoplication, with both pH-MII and endoscopy performed, histology of esophageal biopsies, and off antireflux medications at the moment of examination. GER therapy failure was the indication for surgery. The total number of reflux episodes (acid, nonacidic), bolus and acid clearance time (ACT), and baseline values in distal channels (5–6) were evaluated. Group 1 (G1): patients with EA and fundoplication. Group 2 (G2): patients with EA without fundoplication. T -test was performed to compare results between G1 and G2. Results: Fifteen tracings in EA patients were evaluated. Out of 15, 8 (53%) underwent fundoplication (G1), median age 7.4 years, 87.5% EA type C, 12.5% type A (long gap). Esophagitis was observed in 100% postfundoplication: 2 macroscopic, 1 eosinophilic, 5 microscopic esophagitis. Out of 15, 7 (47%) were EA without fundoplication (G2), median age 3.25 years, 57% EA type C, 43% type A–B. Esophagitis was observed in 85% in G2, all of them microscopic. No statistical differences were observed in pH-MII parameters between both groups. Number of refluxes, ACT, and distal channels (ch-6) were pathological in both groups. Nevertheless better acid clearance and more mucosal damage were observed in G1. Conclusion: In this pediatric series of EA patients, pH-MII data show persistence of GERD even postfundoplication. This observation could be due to severe esophageal dismotility. Even asymptomatic EA patients should undergo monitoring of GER with pH-MII and endoscopy.